Surgical resection for second primary colorectal cancer: a population-based study - Li, Ting; Liu, Zhenyang; Bai, Fei; Xiao, Hua; Zhou, Huijun (Frontiers in Medicine, 2023)
Background: Second primary colorectal cancer (CRC) is attributed to a crucial component of the CRC population. Still, its treatments remain unclear due to the troublesome conditions originating from multiple primary cancers and the lack of quality evidence. This study aimed to determine that which type of surgical resection is the eligible treatment for second primary CRC among patients with a prior cancer history. Method: This cohort study retrospectively collected patients with second primary stage 0-III CRC in the Surveillance, Epidemiology, and End Results database from 2000 to 2017. Prevalence of surgical resection in second primary CRC, overall survival (OS) and disease-specific survival (DSS) of patients who received different surgical interventions were estimated. Results: A total of 38,669 patients with second primary CRC were identified. Most of the patients (93.2%) underwent surgical resection as initial treatment. Approximately 39.2% of the second primary CRCs (N = 15,139) were removed with segmental resection, while 54.0% (N = 20,884) were removed through radical colectomy/proctectomy. Surgical resection was associated with a significantly favorable OS and DSS compared to those not receiving any surgical operations for second primary CRC (OS: adjusted Hazard ratios [adjusted HR]: 0.35; 95% CI: 0.34-0.37, p < 0.001; DSS: adjusted HR: 0.27; 95% CI: 0.25-0.29, p < 0.001). Segmental resection considerably outperformed radical resection in terms of OS and DSS (OS: adjusted HR: 0.97; 95% CI: 0.91-1.00, p = 0.07; DSS: adjusted HR: 0.92; 95% CI: 0.87-0.97, p = 0.002). Segmental resection was also associated with a significantly reduced cumulative mortality of postoperative non-cancer comorbidities. Conclusion: Surgical resection demonstrated excellent oncological superiority for second primary CRC and was used to remove the vast majority of second primary CRCs. In comparison to radical resection, segmental resection offered a better prognosis and reduced postoperative non-cancer complications. The second primary colorectal cancers should be resected if the patients can afford surgical operations.